Loteprednol etabonate for inflammatory conditions of the anterior segment of the eye: twenty years of clinical experience with a retrometabolically designed corticosteroid. (4th March 2018) - Comstock, Timothy L.; Sheppard, John D.
ABSTRACT: Introduction : Topical corticosteroids are an important pharmacotherapy for the management of various inflammatory conditions affecting the anterior segment of the eye. However, medications in this class are associated with well-known risks including increased intraocular pressure (IOP) and development of cataracts. The topical corticosteroid loteprednol etabonate (LE) was developed with the specific intention of minimizing these side effects. Areas covered : The focus of this review is to examine published efficacy and safety data for LE, a drug engineered to undergo rapid metabolism to inactive metabolites with the goal of improved safety. Two decades of clinical research focused on LE formulations are reviewed, including the use of LE in combination with tobramycin. The cumulative body of experience affirms the concept that the molecular design of LE confers certain safety benefits without compromising the desired anti-inflammatory efficacy of a topical corticosteroid. Expert opinion : Loteprednol etabonate is a mainstay for topical therapy of a wide variety of commonplace and niche conditions of the ocular surface and the anterior segment, including in the healing post-operative patient. Its versatility and safety allow eye care providers to recommend both acute induction as well as chronic maintenance therapy with appropriate follow-up.